Sobre a Extração de Fronteiras Culturais Considerando Hábitos Alimentares Observados na Web Social - Silva, Thiago H.; Almeida, Jussara M.; Loureiro, Antonio A. F. (Anais do Workshop sobre Aspectos da Interação Humano-Computador na Web Social (WAIHCWS), 2017)
New approaches to study urban social behavior use Foursquare check-ins to represent user's preferences. In this direction, recently, researchers have proposed a method for identifying cultural boundaries. Our study is based on that methodology, aiming to validate the results and to study some variations. We use a newer dataset to evaluate the results obtained previously. We found that the cultural separation results using our dataset agree with those presented previously. Furthermore, we evaluated the impact of the data observation window size in the results. Finally, we study two additional variations in the studied methodology. The cultural separation quality obtained using these variations is lower compared with the results obtained by the original approach. The results reinforce that, in fact, the methodology originally proposed might be useful to complement large-scale studies on cultural differences. Automatic identification of cultural differences is a valuable information that can enable the reaction of new ubiquitous applications.